2015
DOI: 10.1002/admi.201500375
|View full text |Cite
|
Sign up to set email alerts
|

Atomic Scale Structure and Reduction of Cerium Oxide at the Interface with Platinum

Abstract: A detailed atomic scale description of the interfaces between cerium oxide and metals is necessary for a clear understanding of interfacial interactions, and it may open the way to the optimization of the properties of the combined material in view of its applications. In this study the interface between cerium oxide epitaxial fi lms and the (111) surface of platinum is studied\ud by aberration-corrected scanning transmission electron microscopy and by ab initio density functional theory calculations. Local mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
34
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 47 publications
(62 reference statements)
2
34
1
Order By: Relevance
“…In cerium oxide ultrathin films the interaction with the metallic substrate has been hypothesized to be responsible for the formation of ordered arrays of oxygen vacancies either on the surface 11 of a thin film or at the interface 37 . In the specific case of Pt we have shown that an in-plane lattice contraction is induced by epitaxy in ultrathin films 38 , and we detected a non-negligible Ce 3+ concentration at the interface 35 . The latter effect may certainly modify the surface oxygen vacancy formation energy in thinner films, while it is expected to have a negligible effect on the surface of thicker films, possibly explaining the higher reducibility observed on the 2 ML film.…”
Section: Resultsmentioning
confidence: 58%
“…In cerium oxide ultrathin films the interaction with the metallic substrate has been hypothesized to be responsible for the formation of ordered arrays of oxygen vacancies either on the surface 11 of a thin film or at the interface 37 . In the specific case of Pt we have shown that an in-plane lattice contraction is induced by epitaxy in ultrathin films 38 , and we detected a non-negligible Ce 3+ concentration at the interface 35 . The latter effect may certainly modify the surface oxygen vacancy formation energy in thinner films, while it is expected to have a negligible effect on the surface of thicker films, possibly explaining the higher reducibility observed on the 2 ML film.…”
Section: Resultsmentioning
confidence: 58%
“…The interface electronic configuration was shown to be dominated by charge rearrangements due to electrostatic interactions, but some charge transfer from the substrate to the oxide was also detected [33]. On 3 ML thick films, a different absorption geometry was found to be the most stable, as confirmed by STEM measurements [32]. …”
Section: The Interface Between Cerium Oxide and Metal Surfaces: Epmentioning
confidence: 99%
“…A measurable, though incomplete, reduction has been measured by spatially resolved electron energy loss also for the cerium ions at the interface with the Pt(111) surface [32]. The charge transfer, probably influenced by the metal work function, which is lower for the copper substrate, certainly also modifies other properties in the film, such as its reducibility and reactivity.…”
Section: The Interface Between Cerium Oxide and Metal Surfaces: Epmentioning
confidence: 99%
“…The interface between CeO 2 epitaxial films and the (111) Pt surface is also studied by a combination of AC‐STEM and ab initio density functional theory . A statistical analysis of the size of the coincidence cells indicates that the registering locally changes from 3:4 to 2:3 and 5:7 without a preferential coincidence cell size ( Figure a).…”
Section: Electron Microscopy Characterization Of Ceo2‐based Nanostrucmentioning
confidence: 99%